4(x-6)-9x=

Simple and best practice solution for 4(x-6)-9x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-6)-9x= equation:


4(x-6)-9x=0

We simplify the equation to the form, which is simple to understand
4(x-6)-9x=0

Reorder the terms in parentheses
+(+4x-24)-9x=0

Remove unnecessary parentheses
+4x-24-9x=0

We move all terms containing x to the left and all other terms to the right.
+4x-9x=0+24

We simplify left and right side of the equation.
-5x=+24

We divide both sides of the equation by -5 to get x.
x=-4.8

See similar equations:

| 3x+5=5x+3 | | h=45t-5t^2 | | x^2+54= | | 8x+2x+5=55 | | 5x-50y=-30 | | 8(19x+20)-10x=-11(10-12x) | | 9(8-(-8x-5))=360x+297 | | y^2+28y+187=0 | | (8+x)-(6-3x)= | | x^2-16x+156=0 | | 28=8x+17-7x | | -11.3=22.6 | | -9+8k=-4k | | -17x=-15 | | 3(t+7)+2=6+-2+2t | | 3=-3/2(0)+b | | 3y(5y+9)=6 | | b+2=2(b+2)2-4(b+2)+3/4-(b+2)2 | | 6h+7=17 | | 8(-4+u)=24u | | 6r+7=23+7r | | (x+7)(x+5)=8 | | 16d-(4+5d)=-67 | | 564,2157,9804+548,3256468,375766645654= | | (x-2)45(55x)=105 | | 0=-3/2(3)+b | | 15+n+10=100 | | 6x^2+3x=2 | | -4(2b+1)+(9b-3)=0 | | [-28]-7=4 | | 1=prt*t | | [-28]-7= |

Equations solver categories